A test of the impact of mergers on bank competition. (22nd April 2019) - Cerasi, Vittoria; Chizzolini, Barbara; Ivaldi, Marc
Abstract: We propose a new test to evaluate the impact of horizontal mergers on competition in the banking industry. The test is designed to be applied ex ante to potential mergers while being parsimonious in terms of data, as it only uses information on branches in local markets. The test is a counterfactual exercise based on a two‐stage model where banks compete in branching and interest rates and requires comparing the estimated degree of competition in the status quo, where branching networks by banks are those actually observed, with a counterfactual scenario, where the branching network of the new entity is the sum of the branches of the banks involved in the horizontal merger. The statistical difference between the two estimated measures of competition quantifies the impact of the merger. We apply our test to French and Italian mergers.